Über einige neuseeländische Stratiomyiiden Osten-Sackens im Deutschen Entomologischen Institut in Berlin (Diptera). - Lindner, Erwin (Contributions to Entomology = Beiträge zur Entomologie, 1958)
The author deals with 11 species of Stratiomyiidae (Diptera). He dercribes as new 2 genera and 6 species. Nomenclatural Actsamoena Lindner, 1958 (Australoberis), spec. n.parvula Lindner, 1958 (Dysbiota), spec. n.osten-sackeni Lindner, 1958 (Neoexaireta), spec. n.smaragdina Lindner, 1958 (Neoexaireta), spec. n.venusta Lindner, 1958 (Neoexaireta), spec. n.Australoberis Lindner, 1958 (Stratiomyiidae), gen. n.Dysbiota Lindner, 1958 (Stratiomyiidae), gen. n.